2018
DOI: 10.3892/ijo.2018.4463
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-381 reduces inflammation and infiltration of macrophages in polymyositis via downregulating HMGB1

Abstract: The downregulation of microRNA (miR)-381 has been detected in various diseases. The present study aimed to investigate the effects, and underlying mechanisms of miR-381 on inflammation and macrophage infiltration in polymyositis (PM). A mouse model of experimental autoimmune myositis (EAM) was generated in this study. Hematoxylin and eosin staining was conducted to detect the inflammation of muscle tissues. In addition, ELISA and immunohistochemistry were performed to determine the expression levels of associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…In VSMCs, HMGB1 is known to promote VSMC migration by activating the TLR4/PI3K/Akt pathway 31 and to facilitate smooth muscle cell proliferation by activating c‐Jun 32 . Previous studies report that miR‐381‐3p can repress the expression of inflammatory cytokines, such as TNF‐α and IL‐17, by regulating HMGB1, thereby attenuating the development of neuropathic pain and polymyositis 33,34 . Our data indicated that HMGB1 expression was observably increased in human VSMCs cultured in a high glucose environment, and it was repressed by miR‐381‐3p at the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 53%
“…In VSMCs, HMGB1 is known to promote VSMC migration by activating the TLR4/PI3K/Akt pathway 31 and to facilitate smooth muscle cell proliferation by activating c‐Jun 32 . Previous studies report that miR‐381‐3p can repress the expression of inflammatory cytokines, such as TNF‐α and IL‐17, by regulating HMGB1, thereby attenuating the development of neuropathic pain and polymyositis 33,34 . Our data indicated that HMGB1 expression was observably increased in human VSMCs cultured in a high glucose environment, and it was repressed by miR‐381‐3p at the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 53%
“…a recent study demonstrated that overexpression of mir-381 in raW264.7 cell lines decreased the concentrations of il-1β and TnF-α (42). in addition, mir-381 can reduce inflammation and the infiltration of macrophages by targeting high-mobility group box 1 mrna (43). in addition, mir-381 can regulate notch signaling-mediated cardioprotective effect in cardiomyocytes (44).…”
Section: Discussionmentioning
confidence: 99%
“…It is very possible that downregulation of miR-206–3p by MDI exposure may cause upregulation of CCL2/MCP-1 through direct binding of miR-206–3p to the CCL2/MCP-1 3′UTR; further study of this phenomenon is needed. Recently, miR-381–3p has been shown to target the high mobility group box 1 (HMGB1) gene resulting in reduced macrophage mobility and infiltration in polymyositis (Liu et al, 2018). HMGB1 is a highly conserved DNA binding protein that is an important modulator of immune and inflammatory responses in airway inflammation (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%